2020
DOI: 10.1016/j.coviro.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Influenza D virus

Abstract: Influenza D is the only type of influenza virus that mainly affects cattle with frequent spillover to other species. Since the initial description of influenza D virus (IDV) in 2011, the virus has been found to circulate among cattle and swine populations worldwide. Research conducted during the past several years has led to an increased understanding of this novel influenza virus with bovines as a reservoir. In this review, we describe the current knowledge of epidemiology and host range of IDV followed by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Dane et al., 2019; Ferguson et al., 2015, 2018; Flynn et al., 2018; Gaudino et al., 2020; Gorin et al., 2019; Murakami et al., 2019; Nedland et al., 2018; O'Donovan et al., 2019; Oliva et al., 2019; Salem et al., 2017; Silveira et al., 2019; Snoeck et al., 2018). A review paper proposed the cattle as reservoir and amplification host with periodic spill over to other hosts listed before (Liu et al., 2020). In addition, a recent study identified IDV genome in Asian poultry farm aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…Dane et al., 2019; Ferguson et al., 2015, 2018; Flynn et al., 2018; Gaudino et al., 2020; Gorin et al., 2019; Murakami et al., 2019; Nedland et al., 2018; O'Donovan et al., 2019; Oliva et al., 2019; Salem et al., 2017; Silveira et al., 2019; Snoeck et al., 2018). A review paper proposed the cattle as reservoir and amplification host with periodic spill over to other hosts listed before (Liu et al., 2020). In addition, a recent study identified IDV genome in Asian poultry farm aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…The homology of amino acid sequences between IDV and ICV is roughly 50%, however, the distance between the two influenza viruses is similar to the one found between influenza A and B viruses (IAVs, IBVs). 2,3 No cross-reactivity has been detected between IDV and ICV. 4 Although the virus has been first isolated in swine, several epidemiological and serological studies support the hypothesis that cattle represent the natural reservoir of IDV with periodical spillover events to other animal hosts (i.e., camel, sheep, swine, horse, goat).…”
mentioning
confidence: 98%
“…[19][20][21]. There are four types of influenza viruses: influenza A, B, C, and D. However, influenza A (H1N1 and H3N2) and influenza B are the main influenza viruses that cause current seasonal influenza [22][23][24]. Although in clinical diagnosis, influenza cannot be easily distinguished from other acute respiratory illnesses, such as common cold, bronchitis, or viral pneumonia, etc., influenza is usually more serious than the common cold, and the duration of treatment is longer than the common cold.…”
Section: The Definition Of Influenza-like Illnessesmentioning
confidence: 99%